Self-piercing riveting connections using aluminium rivets - Hoang, N.-H.; Porcaro, R.; Langseth, M.; Hanssen, A.-G. (International journal of solids and structures, 2010)
The development of the self-piercing riveting (SPR) technology in recent years has broadened the application of the technology in the automobile industry. However, the SPR process currently utilises high-strength steel rivets; and the combination between steel rivets with an aluminium car body makes recycling a challenge. The possibility of replacing a steel self-piercing rivet with an aluminium one has thus been raised as an interesting topic. Within this framework, the objective of the present paper is to provide an experimental database on the riveting process using an aluminium self-piercing rivet. An experimental programme has been carried out, where two similar sheets in aluminium alloy 6060 in three different tempers (temper W, temper T4, and temper T6) have been joined by using a self-piercing rivet in three different alloys, i.e. 6082-T6, 7108-T5, and 7278-T6. The influence of the die shape on the SPR of aluminium sheets using aluminium rivets was also considered. Conventional rivets and dies according to the Boellhoff standards were employed. The test results were exploited in terms of the riveting force–displacement curves and cross-sectional geometries of the riveted joints. The test data were also used to validate a 2D-axisymmetric model, which was originally developed at SIMLab for modelling the riveting process using a steel rivet. Finally, the mechanical behaviour of a riveted connection using an aluminium rivet under quasi-static loading conditions (i.e. combined pure shear and pure opening loads) was experimentally studied and compared with corresponding tests using a steel rivet in terms of force–displacement curves.